Całościowa wizja człowieka i świata z punktu widzenia psychosyntezy = The vision of wholeness from the viewpoint of psychosynthesis - Białek, Ewa (Zielona Góra: Uniwersytet Zielonogórski)
Understanding relations between objects, and perceiving the nature of reality in which we live not as material, but spiritual, recognizing certain higher order, understanding the meaning of life, as opposed to chaos, we are prompted, or obliged even, to re-examine the way we think about everything that surrounds us in the categories of balanced development and health. Such a perspective seems to be a necessity now, given the current state of health of the individual, the family, societies and the world, including the pollution of the natural environment
Keywords: filozofia nauki; psychosynteza